2006
DOI: 10.1021/la062001w
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Structure in Oil-in-Water Emulsions As Studied by Diffusing Wave Spectroscopy

Abstract: Transitions in structure of sodium caseinate stabilized emulsions were studied using conventional rheometry as well as diffusing wave spectroscopy (DWS). Structural differences were induced by different amounts of stabilizer, and transitions in structure were induced by acidification. Special attention was given to the sol-gel transition. In this study the criterion of the sol-gel transition being frequency independent was verified for emulsions using DWS. It was shown that this sol-gel transition did not corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 27 publications
4
32
0
Order By: Relevance
“…This suggested that adding more HMP does not change the structure of the flocs much, but simply crowded the separated phases. A similar observation was reported for depletion flocculation of emulsion droplets with added xanthan (0-0.2%) 8,9,24 and HMP. Statistical analysis of the data of ultrasonic attenuation as a function of concentration of HMP indicated that there was an effect of pectin type on the values of attenuation, although the overall trend is the same.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…This suggested that adding more HMP does not change the structure of the flocs much, but simply crowded the separated phases. A similar observation was reported for depletion flocculation of emulsion droplets with added xanthan (0-0.2%) 8,9,24 and HMP. Statistical analysis of the data of ultrasonic attenuation as a function of concentration of HMP indicated that there was an effect of pectin type on the values of attenuation, although the overall trend is the same.…”
Section: Resultssupporting
confidence: 86%
“…5,7 During acidification with glucono-δ-lactone (GDL), the pH is gradually lowered, and at a pH <5.0, the steric stabilizing layer of casein micelles collapses, there is a decrease in charge repulsion, and the caseins aggregate (Liu et al, submitted). 8,9 It has been demonstrated that the interactions between HMP and casein micelles are pH-dependent and occur at pH of about 5. The HMP adsorbed on the casein micelles prevents sedimentation via electrostatic and steric stabilization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of sodium caseinate emulsions, it was found that diffusing wave spectroscopy is a very useful technique to measure the different structural transitions that take place within the system. It was found that two transitions took place in a system with an excess of stabilizer [43] .…”
Section: Micellesmentioning
confidence: 99%